Haptic Assessment in Fabrics with Kansei Evaluation - Nazlina, Shaari (IEEE, 2011)
Today's consumers demand more of what will enrich their life. They desire new products that could fulfill their needs. With the reference to the changing society and consumer -oriented trends, design today takes place in a different framework than ever before. This is where human perceptive faculties consist of five senses: visual, auditory, olfactory, taste, and tactile sense are involved. Visual is the most powerful sense for human perception followed by the auditory sense. This article attempts to find the connection between the visual and the auditory senses. In particular, the aim is to evaluate tactile evaluation, involved with the haptic experience in identifying the preferable materials for clothing. The research will propose methods in Kansei to facilitate the understanding of the different types of haptic activities involved in this testing. These structures clearly recognize and evoke specific elements in fabrics appearances and its semantic values.